2002
DOI: 10.1017/s1047951102000318
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide can be a useful biochemical marker for myocarditis in patients with Kawasaki disease

Abstract: The mean concentration of brain natriuretic peptide in the plasma was 73.2 +/- 107.7 (mean +/- SD) pg/ml in the acute phase, and 7.9 +/- 7.5 pg/ml in the convalescent phase. We checked the electrocardiograms to find abnormal Q waves, elevation or depression of the ST segments, change in the pattern of the QRS complexes, and flattening or inversion of the T wave, all believed to be markers of myocarditis in Kawasaki disease. Those in whom the concentrations were greater than 50 pg/ml in the acute phase showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Kawamura et al maintain that pro-inflammatory cytokines, such as interleukin-1 and TNF-, cause myocarditis and stimulate secretion of BNP in acute KD. 17 They also reported no significant correlation between plasma BNP level and LV ejection fraction (LVEF) in acute KD. In contrast, in the present study, LVSF, VCFc, and Sw in week 1 significantly correlated with plasma BNP level.…”
Section: Plasma Bnp Level In Acute Kdmentioning
confidence: 98%
See 2 more Smart Citations
“…Kawamura et al maintain that pro-inflammatory cytokines, such as interleukin-1 and TNF-, cause myocarditis and stimulate secretion of BNP in acute KD. 17 They also reported no significant correlation between plasma BNP level and LV ejection fraction (LVEF) in acute KD. In contrast, in the present study, LVSF, VCFc, and Sw in week 1 significantly correlated with plasma BNP level.…”
Section: Plasma Bnp Level In Acute Kdmentioning
confidence: 98%
“…17 The mechanism responsible for the increased plasma BNP level in acute KD is not yet known. Kawamura et al maintain that pro-inflammatory cytokines, such as interleukin-1 and TNF-, cause myocarditis and stimulate secretion of BNP in acute KD.…”
Section: Plasma Bnp Level In Acute Kdmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported left ventricular diastolic dysfunction in KD patients during the acute phase based on the inflow Doppler and tissue Doppler profiles of the left ventricle [11,12]. These reports concluded that diastolic dysfunction might contribute to the increased brain natriuretic peptide (BNP) levels seen in these patients [13]. Another study by Arnold et al reported late diastolic impairment (10.6 ± 5.1 years from the onset of KD) in segments supplied by stenotic coronary arteries without any evidence of systolic dysfunction in KD patients who had a coronary artery dilation/aneurysm defined as a coronary artery diameter N3 mm by angiogram during the acute phase of the disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…Elevation has been reported with diverse causes, including Chagas disease, 80 Kawasaki disease, 81 viral myocarditis, 82 Duchenne muscular dystrophy and its carrier state, 83 and myocardial cytotoxicity during chemotherapy, 84 stem cell therapy, 85 and after bone marrow transplantation. 86 A recent investigation by the Framingham Heart Study reported that plasma BNP predicted a wide range of cardiovascular events, including heart failure, atrial fibrillation, stroke, transient ischemic attack, and death.…”
Section: Brain Natriuretic Peptide In Cardiovascular Diseases Other Tmentioning
confidence: 99%